Prevalence of colistin resistance and antibacterial resistance in commensal Escherichia coli from chickens: An assessment of the impact of regulatory intervention in South Africa - Ibrahim Z. Hassan; Daniel N. Qekwana; Vinny Naidoo (Veterinary Medicine and Science, 2024)
Abstract Background Antimicrobial resistance (AMR) is a global health problem largely due to the overuse of antimicrobials. In recognition of this, the World Health Assembly in 2015 agreed on a global action plan to tackle AMR. Following the global emergence of the mcr‐1‐associated colistin resistance gene in the livestock industry in 2016, several countries including South Africa restricted the veterinary use of colistin as the gene threatens the clinical utility of the drug. This study is a follow‐up to the restriction in place in order to evaluate the impact of such policy adoption. Objective To assess the prevalence of antibacterial resistance (ABR), and the mcr‐1 colistin resistance gene in broiler chicken over a 2‐year period, as a follow‐up to the veterinary ban on colistin use in South Africa. Methods A total of 520 swab samples were obtained during 2019 (March–April) and 2020 (February–March), from healthy broiler chicken carcasses (n = 20) and chicken droppings in transport crates (n = 20) at various poultry abattoirs (N = 7) in the Gauteng province of South Africa. Escherichia coli organisms were isolated and subjected to a panel of 24 antibacterials using the MicroScan machine. Screening for mcr‐1 colistin resistance gene was undertaken using PCR. Result Four hundred and thirty‐eight (438) E. coli strains were recovered and none demonstrated phenotypic resistance towards colistin, amikacin, carbapenems, tigecycline and piperacillin/tazobactam. The mcr‐1 gene was not detected in any of the isolates tested. Resistances to the aminoglycosides (0%–9.8%) and fluoroquinolones (0%–18.9%) were generally low. Resistances to ampicillin (32%–39.3%) and trimethoprim/sulphamethoxazole (30.6%–3.6%) were fairly high. A significant (p < 0.05) increase in cephalosporins and cephamycin resistance was noted in the year 2020 (February–March) when compared with the year 2019 (March–April). Conclusion The absence of mcr‐1 gene and colistin resistance suggests that mitigation strategies adopted were effective and clearly demonstrated the significance of regulatory interventions in reducing resistance to critical drugs. Despite the drawback in regulatory framework such as free farmers access to antimicrobials OTC and a dual registration system in place, there is a general decline in the prevalence of ABR when the present data are compared with the last national veterinary surveillance on AMR (SANVAD 2007). To further drive resistance down, mitigation strategies should focus on strengthening regulatory framework, the withdrawal of OTC dispensing of antimicrobials, capping volumes of antimicrobials, banning growth promoters and investing on routine surveillance/monitoring of AMR and antimicrobial consumption.